STRATEGI KEPALA SEKOLAH DALAM MEMOTIVASI GURU DI SMPN KECAMATAN AIR HANGAT BARAT KEBUPATEN KERINCI - Anggun Febya Anesti; Anisah Anisah; Yuskal Kusman (Journal of Educational Administration and Leadership, 2020)
This study aims to determine teacher perceptions about the strategy of motivation giving by leaders in junior high school in Air Hangat Barat Subdistrict, Kerinci, which includes :1) Behavior (action), 2) Applying Reward and Punishment, 3) Participation (empomering power). Population in this study are teacher who are in junior high school of Air Hangat Barat Subdistrict, Kerinci amounted to 104 people. The sample in this study amounted to 49 people that determined using stratified sampling and taken by proportional random sampling taken based on the cochran formula. Data collection tool was a questionnaire with likert scale models that have proven validity and reliability. The findings show that the strategy of motivation giving by leader be going in good category from some aspects :1) Behavior (action) with average score 88,99%, 2 )Applying Reward and Punishment with an average score 89,47% and 3) Participation (empomering power) with an average score 91,21% The result show that teacher perceptions about the strategy of motivation giving by leader in junior high school of Air Hangat Barat Subdistrict, Kerinci are in fairly good category with score of 89,90%.